Clinical picture, diagnosis, and treatment of gingival cyst: A narrative review - Patrycja Tarka; Piotr Wlodarczyk; Daniel Hafzi; Peer Steinsvoll; Iwona Olszewska-Czyz (Journal of Stomatology)
Gingival cyst of adult (GCA) is a rare developmental cyst of odontogenic origin. It occurs in free or attached gingiva, usually near buccal canine and premolar mandibular region. It is commonly asymptomatic, slow-growing, single, and small, flesh-colored swelling. GCA is usually treated by excisional biopsy. The aim of the review was to summarize knowledge about the etiology, symptoms, diagnosis, and treatment of GCA available in scientific literature. PubMed and Google Scholar databases were used as sources, and key words and their combinations, such as “gingival cyst” and “odontogenic cysts” were applied to obtain the list of available references. The literature on GCA indicated that this relatively rare developmental odontogenic cyst is mostly prevalent in the 5th and 6th decade, most frequently in the mandible and canine-premolar sites, typically presenting as solitary lesion of 5 mm diameter, treated by excisional biopsy. Histology shows a very thin, uninflamed wall, lined with a squamous or cuboidal epithelium. Multiple cysts are very rare. The incidence of GCA has been reported to be less than 0.5%. It can cause pressure and bone resorption. Definitive treatment can be achieved with excisional biopsy. Despite being a rare lesion, GCA should be considered in clinical differential diagnosis of gingival lesions.